EFFECTIVENESS OF COMPARATIVE GOAT MANURE FERTILIZER ON THE GROWTH OF COFFEE SEEDS FROM ARABICA VARIETIES (Coffea arabica L) - Meko Gustian; Sri Wulandari; Darwan Effendi; Mardia Apriansi; Adnan Adnan; Anggri Pratama (Fakultas Pertanian Universitas Ratu Samban, 2022)
Seed quality is determined by good seedling techniques, one of which is the use of planting media. Where the planting media can use soil media with animal waste. The purpose of this study to determine the effectiveness of goat manure seedling media on the growth of Arabica coffee seedlings and to obtain the best comparison of goat manure seedling media on the accretion of Arabica coffee seedlings. This research method used a completely randomized design consisting of one factor and four treatments, namely soil 1:0 (M0), soil + goat manure 1:1 (M1), soil + goat manure 1:2 (M2), and soil + goat Manure 1:3 (M3). Variables observed: percentage, plant height, number of leaves. The data obtained were analyzed using the ANOVA if significantly continued with DMRT at the 5% level. The results showed the effectiveness of goat manure seedling media on the growth of arabica coffee seedlings, with a growth percentage of 97%. The best comparison of goat manure seedling media on the growth parameters of arabica coffee seedlings in the M3 treatment with a mixture of soil and goat manure ratio (1:3), the average plant height (14.19 cm), and the number of leaves (7.0 strands).